Microneedle-Mediated Transdermal Delivery of Biopharmaceuticals - Hiep X. Nguyen; Chien N. Nguyen (MDPI AG, 2023)
Transdermal delivery provides numerous benefits over conventional routes of administration. However, this strategy is generally limited to a few molecules with specific physicochemical properties (low molecular weight, high potency, and moderate lipophilicity) due to the barrier function of the stratum corneum layer. Researchers have developed several physical enhancement techniques to expand the applications of the transdermal field; among these, microneedle technology has recently emerged as a promising platform to deliver therapeutic agents of any size into and across the skin. Typically, hydrophilic biomolecules cannot penetrate the skin by passive diffusion. Microneedle insertion disrupts skin integrity and compromises its protective function, thus creating pathways (microchannels) for enhanced permeation of macromolecules. Microneedles not only improve stability but also enhance skin delivery of various biomolecules. Academic institutions and industrial companies have invested substantial resources in the development of microneedle systems for biopharmaceutical delivery. This review article summarizes the most recent research to provide a comprehensive discussion about microneedle-mediated delivery of macromolecules, covering various topics from the introduction of the skin, transdermal delivery, microneedles, and biopharmaceuticals (current status, conventional administration, and stability issues), to different microneedle types, clinical trials, safety and acceptability of microneedles, manufacturing and regulatory issues, and the future of microneedle technology.